Penerapan Media Youtube “Aku Paham” Dalam Pembelajaran Teks Biografi Kelas X SMK Negeri 6 Semarang - Nisa, Erika Wahidatun; Asropah, Asropah; Septiana, Ika; Warkito, Petrus Joko (Universitas Negeri Padang, 2024)
This study evaluates the use of YouTube in learning biographical texts in class X of SMK Negeri 6 Semarang, focusing on its impact on student engagement and understanding. Educational videos from YouTube, combined with the Problem Based Learning (PBL) model, enhance students' active learning and critical thinking skills. This study applies a qualitative descriptive method to evaluate the use of the YouTube video